Serum hepatocyte apoptosis biomarker predicts the presence of significant histological lesion in chronic hepatitis B virus infection. Issue 12 (December 2016) - Cao, Zhu-Jun; Li, Jing; Wang, Yun; Bao, Rebecca; Liu, Yu-Han; Xiang, Xiao-Gang; Lin, Lan-Yi; Ye, Fu-Xiang; Lu, Jie; Xie, Qing; Bao, Shi-San; Wang, Hui
Abstract: Background: Hepatocyte death, either apoptosis or necrosis, is closely associated with hepatic inflammation and fibrosis. Aims: To investigate the potential values of hepatocytes death biomarker, M30 (apoptosis) and M65 (total death) in predicting histological lesions in chronic hepatitis B virus (HBV) infection. Methods: Total 201 treatment-naïve patients were prospectively recruited. Liver biopsies were performed prior to antiviral treatments for treatments starting evaluation. Sera were collected on the day of liver biopsy for biomarker measurements. Sera from 200 age-matched healthy volunteers served as healthy controls (HCs). Results: Significant histological lesions (SHL, i.e. significant inflammation and/or significant fibrosis) were confirmed in 150 (74.63%) patients. There were significantly higher serum M30 and M65 in patients with SHL than those without SHL ( p  < 0.001) or than HCs ( p  < 0.001). Serum M30, but not M65, independently predicted SHL [odds ratio:3.4 (95% CI, 1.8–6.2) per increase of 50 U/L, p  < 0.001] after adjusting other potential confounding factors. A novel model based on M30 provided good diagnostic performance in predicting SHL [AUC, 0.87 (0.81–0.92)]. Cut-off value of >0 to confirm or ≤−0.5 to exclude SHL has ∼12% misclassification rate. Conclusion: Hepatocyte apoptosis biomarker, M30 is a promising non-invasive alternative to liver biopsy in chronic HBV infection upon treatment evaluation.